Efficacy of a Trivalent Hand, Foot, and Mouth Disease Vaccine against Enterovirus 71 and Coxsackieviruses A16 and A6 in Mice - Elizabeth A. Caine; Jeremy Fuchs; Subash C. Das; Charalambos D. Partidos; Jorge E. Osorio (Viruses, 2015)
Hand, foot, and mouth disease (HFMD) has recently emerged as a major public health concern across the Asian-Pacific region. Enterovirus 71 (EV71) and Coxsackievirus A16 (CVA16) are the primary causative agents of HFMD, but other members of the Enterovirus A species, including Coxsackievirus A6 (CVA6), can cause disease. The lack of small animal models for these viruses have hampered the development of a licensed HFMD vaccine or antivirals. We have previously reported on the development of a mouse model for EV71 and demonstrated the protective efficacy of an inactivated EV71 vaccine candidate. Here, mouse-adapted strains of CVA16 and CVA6 were produced by sequential passage of the viruses through mice deficient in interferon (IFN) α/β (A129) and α/β and γ (AG129) receptors. Adapted viruses were capable of infecting 3 week-old A129 (CVA6) and 12 week-old AG129 (CVA16) mice. Accordingly, these models were used in active and passive immunization studies to test the efficacy of a trivalent vaccine candidate containing inactivated EV71, CVA16, and CVA6. Full protection from lethal challenge against EV71 and CVA16 was observed in trivalent vaccinated groups. In contrast, monovalent vaccinated groups with non-homologous challenges failed to cross protect. Protection from CVA6 challenge was accomplished through a passive transfer study involving serum raised against the trivalent vaccine. These animal models will be useful for future studies on HFMD related pathogenesis and the efficacy of vaccine candidates.